Handbook of Labor, Human Resources and Population Economics 2021
DOI: 10.1007/978-3-319-57365-6_205-1
|View full text |Cite
|
Sign up to set email alerts
|

Unions, Worker Participation, and Worker Well-being

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Nevertheless, the meta-study by Laroche (2016: 735) concluded that, taken as a whole (including panel studies), the evidence for this negative association was "comparatively weak." Other reviews since Laroche have been able to track a more nuanced set of findings (e.g., Artz and Heywood, 2022). More importantly, one focus of recent research has served to shift attention toward expecting a present-day positive partial correlation between union membership and well-being while confirming findings from an earlier epoch of the negative partial correlation reported by Freeman.…”
Section: The Direction Of Associationmentioning
confidence: 95%
“…Nevertheless, the meta-study by Laroche (2016: 735) concluded that, taken as a whole (including panel studies), the evidence for this negative association was "comparatively weak." Other reviews since Laroche have been able to track a more nuanced set of findings (e.g., Artz and Heywood, 2022). More importantly, one focus of recent research has served to shift attention toward expecting a present-day positive partial correlation between union membership and well-being while confirming findings from an earlier epoch of the negative partial correlation reported by Freeman.…”
Section: The Direction Of Associationmentioning
confidence: 95%
“…The evidence in this respect appears to be mixed when comparing the findings for Britain (Bender and Sloane 1999) and the USA (Brochu and Morin 2012), although one would expect decreasing job insecurity when workers enter a trade union. In this context, researchers like Guest and Conway (2004) refer to the phenomenon of the dissatisfied union member, which has been discussed intensively in the literature (see Laroche (2016) for a meta‐analysis, and Artz and Heywood (2021) and Goerke (2021) for recent surveys). One explanation for this phenomenon could be that trade unions raise expectations.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of studies, for example, considered in the meta-analysis by Laroche (2016) and the surveys by Hammer and Avgar (2005), Artz and Heywood (2021), and Goerke (2021), are based on data from the UK and the US. Given the specificity of their industrial relations system, we cannot easily generalise the findings.…”
Section: Introductionmentioning
confidence: 99%